Stem Coloration in Alfalfa: Anthocyanin Accumulation Patterns and Nutrient Profiles of Red- and Green-Stemmed Variants - Zhengfeng Cao; Jiaqing Li; Chuanjie Wang; Xueyang Min; Zhenwu Wei (Agronomy)
Anthocyanins, crucial flavonoids in plants, enhance stress tolerance in alfalfa and are attracting attention due to their antioxidant properties. This study analyzed red- and green-stemmed alfalfa using spectrophotometry, frozen sections, and LC-MS/MS. Anthocyanins were concentrated in stem vascular cambium, with red stems peaking at 61.08 mg g−1 DW during the bud stage. Seven anthocyanidins were identified, with their corresponding aglycones including cyanidin, peonidin, and malvidin. At early flowering, red-stemmed alfalfa contained 35 classes of anthocyanins compared to 17 in green-stemmed varieties, with cyanidin-3-O-glucoside levels significantly higher in red stems (4.423 μg g−1, p < 0.05). Red-stemmed alfalfa also showed higher contents of acid detergent fiber, crude fat, Cu, Fe, and Zn (p < 0.05), especially Zn (p < 0.01). Correlation analysis revealed a strong positive link between cyanidin and crude fat (Spearman’s ρ = 0.93, p < 0.01) and a significant negative correlation with neutral detergent fiber (ρ = −0.88, p < 0.05). Cyanidin and peonidin are associated with stem color differentiation, with cyanidin contributing predominantly to red pigmentation, whereas zinc and crude fat exhibit a synergistic correlation with anthocyanin accumulation. These findings may inform breeding strategies to develop anthocyanin-enriched alfalfa.